Sinkretisme Islam Jawa dalam Perlawanan Kassan Moekmin terhadap Belanda di Gedangan Sidoarjo 1904 M - Zakariah, Irfan; Muhsin, Imam (Historia Madania: Jurnal Ilmu Sejarah, 2024)
This study aims to analyze the unification of Javanese beliefs with Islam from Kassan Moekmin in carrying out resistance against Dutch colonialism in Gedangan Sidoarjo in 1904 AD. This research uses historical research methods consisting of heuristics, criticism, interpretation and historiography with an anthropological approach. Kassan Moekmin is a mat trader who trades from Pekalongan, Semarang, to Mojokerto. During his overseas study, he studied with kiai Ngabdoeroesoel from Krapjak, Haji Muhammad Tahir from Krian, and Haji Idris from Mojokerto. He is famous as a suwuk expert. During his time of fame, Kassan Moekmin was declared Eru Tjokro or Ratu Adil, who Joyoboyo described as the saviour king of Java. He also considers himself to be Imam Mahdi according to Islamic beliefs. He gave confidence to his followers through rituals and objects that he blessed to fight against the Dutch. Kassan Moekmin and his followers then fought against the Dutch in Gedangan Sidoarjo in 1904 AD.